From Bureaucracy to Algorithms: A Transformative Analysis of the Future of Management in the Age of Artificial Intelligence - Sakher Farea Ghalib Al-Junaid (Cita konsultindo, 2026)
This study investigates the radical transformation in organizational systems from the traditional bureaucratic model to an